Atomic force microscopy methodology and AFMech Suite software for nanomechanics on heterogeneous soft materials - Galluzzi, Massimiliano (Nat Commun, 2018)
Atomic force microscopy has proven to be a valuable technique to characterize the mechanical and morphological properties of heterogeneous soft materials such as biological specimens in liquid environment. Here we propose a 3-step method in order to investigate biological specimens where heterogeneity hinder a quantitative characterization: (1) precise AFM calibration, (2) nano-indentation in force volume mode, (3) array of finite element simulations built from AFM indentation events. We combine simulations to determine internal geometries, multi-layer material properties, and interfacial friction. In order to easily perform this analysis from raw AFM data to simulation comparison, we propose a standalone software, AFMech Suite comprising five interacting interfaces for simultaneous calibration, morphology, adhesion, mechanical, and simulation analysis. We test the methodology on soft hydrogels with hard spherical inclusions, as a soft-matter model system. Finally, we apply the method on E. coli bacteria supported on soft/hard hydrogels to prove usefulness in biological field.